2014
DOI: 10.1038/ncomms6453
|View full text |Cite
|
Sign up to set email alerts
|

Seismic reflection data support episodic and simultaneous growth of the Tibetan Plateau since 25 Myr

Abstract: The spectacular topography of the Tibetan Plateau is the result of collision between India and Eurasia over some 50 Myr, but how the plateau grew to its present size remains a topic of debate. Work along its eastern margin suggests a two-stage uplift (thus growth of the plateau) since 30-25 Myr. Here we report high-resolution seismic reflection and drill core results from the southern Tarim Basin that indicate a similar pattern for the northern margin of the plateau. The data suggest that uplift in northern Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…The high‐quality strike‐perpendicular seismic reflection profile that directly crosses the coseismic slip patch allows us to study the long‐term development of the fold and thrust structures at Pishan (section 4). The constant thickness of the Paleogene to early Pliocene sediments overlying the fault indicates that they predate the onset of folding at ≤3.6 Ma and therefore show the full cumulative displacement since that time (Jiang & Li, ; Li et al, ). They form a monocline with the southern limb dipping to the north slightly more steeply than the northern limb (Figure ) and with a wavelength noticeably shorter than the topographic anticline—its two hinge axes are only 3 km apart (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐quality strike‐perpendicular seismic reflection profile that directly crosses the coseismic slip patch allows us to study the long‐term development of the fold and thrust structures at Pishan (section 4). The constant thickness of the Paleogene to early Pliocene sediments overlying the fault indicates that they predate the onset of folding at ≤3.6 Ma and therefore show the full cumulative displacement since that time (Jiang & Li, ; Li et al, ). They form a monocline with the southern limb dipping to the north slightly more steeply than the northern limb (Figure ) and with a wavelength noticeably shorter than the topographic anticline—its two hinge axes are only 3 km apart (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Across the northern range front of the Western Kunlun Mountains the elevation changes rapidly from 5,000 m to 2,100 m within a horizontal distance of just 50 km, and post‐Mesozoic basin sediments have a thickness of around 10 km (Jiang & Li, ; Wei et al, ). The most basinward active shortening visible at the surface is in the low‐lying, gently northward sloping piedmont.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The Western Kunlun is characterized by high altitudes, and erosion of this growing topography over the last ~23 Myr has significantly contributed to the filling of the presently endorheic Tarim foreland basin (Figure ), with Cenozoic sediment thicknesses of up to ~8–9 km along the topographic mountain front (e.g., D. S. Li et al, ; Métivier & Gaudemer, ; Wei et al, ). Inside this basin, growth strata in sedimentary series probably younger than 10–15 Ma have been observed on seismic profiles above faults and folds of the mountain front (Guan et al, ; Jiang & Li, ; T. Li et al, ; C. Y. Wang et al, ; Wei et al, ). This clearly indicates that the mountain range was deforming during the late Cenozoic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the time and mechanism of crustal thickening and initial surface uplift of the Tibetan Plateau remain highly controversial. Previous studies have suggested that the initiation of surface uplift started in a variety of different epoches ranging from Eocene to Pliocene (45–4.5 Ma) [ Chung et al , ; Deng et al , ; Dupont‐Nivet et al , , ; Ge et al , ; Jiang and Li , ; Kent‐Corson et al , ; Rowley and Currie , ; C. Wang et al , ; Wang et al , ; Zheng et al , ]. Likewise, the estimated time for crustal thickening ranges from Eocene to Miocene (45–10 Ma) [ Chung et al , , , ; Guan et al , ; Z. Guo et al , ; Harris and Massey , ; Harrison et al , ; Hou et al , , ; Ji et al , ; Jiang and Li , ; Jiang et al , ; Le Fort et al , ; Ma et al , ; Tapponnier et al , ; Q. Wang et al , , ; Zhang et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the initiation of surface uplift started in a variety of different epoches ranging from Eocene to Pliocene (45–4.5 Ma) [ Chung et al , ; Deng et al , ; Dupont‐Nivet et al , , ; Ge et al , ; Jiang and Li , ; Kent‐Corson et al , ; Rowley and Currie , ; C. Wang et al , ; Wang et al , ; Zheng et al , ]. Likewise, the estimated time for crustal thickening ranges from Eocene to Miocene (45–10 Ma) [ Chung et al , , , ; Guan et al , ; Z. Guo et al , ; Harris and Massey , ; Harrison et al , ; Hou et al , , ; Ji et al , ; Jiang and Li , ; Jiang et al , ; Le Fort et al , ; Ma et al , ; Tapponnier et al , ; Q. Wang et al , , ; Zhang et al , ]. Two main mechanisms have been proposed to account for crustal thickening and the surface uplift of the Tibetan Plateau: (i) continuous thickening and widespread viscous flow of the crust and mantle of the entire plateau, which assumes the entire lithosphere thickened as a thin viscous sheet, with broadly distributed shortening of both crust and mantle having absorbed plate convergence, i.e., a “soft Tibet model” [ England and Houseman , ; Molnar et al , ], and (ii) tectonic thickening, which proposes that plate convergence was consumed by time‐dependent, localized shear between coherent lithospheric blocks, i.e., a “rigid Tibet model” [ Jiang and Li , ; Jiang et al , ; Tapponnier et al , ; Yin and Harrison , ].…”
Section: Introductionmentioning
confidence: 99%